Maturity of Internal Control System, the Capability of Internal Auditors, and Performance Accountability in Local Governments - Rahmasari, Arttika; Setiawan, Doddy (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2022)
While research on the accountability of local government performance has grown significantly, little attention has been paid to the critical success factors, particularly the role of the maturity of the government's internal control system and the capability of the government's internal auditors. This study examines the effect of the maturity of the government's internal control system and the capability of the government's internal auditors on the accountability of local government performance, with control variables, namely audit opinion, local own-source revenues, and proliferation status. It aims to fill the gap using the Indonesian case. This study uses secondary data with sample selection using the purposive sampling method. Local governments in Indonesia from 2017 to 2019 are used as samples. The results of this study indicate that the government's internal control system's maturity, internal auditors' capability, and audit opinions positively affect local governments' performance accountability. In contrast, local own-source revenues and proliferation status negatively impact local governments' performance accountability. The implication of this study is to increase the accountability of local government's performance and continue to improve the maturity of the government's internal control system to achieve at least level 3 (Integrated). The capability of internal government auditors needs to achieve at least level 3 (Defined); thereby, the internal control function of local governments can be optimal.